2021
DOI: 10.1080/07391102.2021.1934544
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights of the conserved “priming loop” of hepatitis B virus pre-genomic RNA

Abstract: Initiation of protein-primed (-) strand DNA synthesis in hepatitis B virus (HBV) requires interaction of the viral polymerase with a cis-acting regulatory signal, designated epsilon (e), located at the 5 0 -end of its pre-genomic RNA (pgRNA). Binding of polymerase to e is also necessary for pgRNA encapsidation. While the mechanistic basis of this interaction remains elusive, mutagenesis studies suggest its internal 6-nt "priming loop" provides an important structural contribution. e might therefore be consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(78 citation statements)
references
References 56 publications
4
73
1
Order By: Relevance
“…Palbociclib binds to HIV TAR with a KD of 100-300 nM, depending on ionic conditions, comparable to its reported affinity for cdk6 (KD ~60nM) 24 , which was only achieved following a decade-long medicinal chemistry effort. Other studies have reported binding of FDA approved drugs to RNA [42][43][44] , including kinase inhibitors 45 , but binding in these cases was 100-1,000 fold weaker than we observe 25 or non-specific 46,47 . It is sometimes stated that kinase inhibitors make good RNA binding molecules, but we have shown that RNA binding can be obtained fully independently of kinase inhibition.…”
Section: Discussioncontrasting
confidence: 89%
“…Palbociclib binds to HIV TAR with a KD of 100-300 nM, depending on ionic conditions, comparable to its reported affinity for cdk6 (KD ~60nM) 24 , which was only achieved following a decade-long medicinal chemistry effort. Other studies have reported binding of FDA approved drugs to RNA [42][43][44] , including kinase inhibitors 45 , but binding in these cases was 100-1,000 fold weaker than we observe 25 or non-specific 46,47 . It is sometimes stated that kinase inhibitors make good RNA binding molecules, but we have shown that RNA binding can be obtained fully independently of kinase inhibition.…”
Section: Discussioncontrasting
confidence: 89%
“…The HBV ε RNA stem-loop that templates DNA priming [PDB: 6VAR (45)] was also docked into the full-length model of genotype B P (Figs. 5C and S29A-C).…”
Section: The Fingers Subdomain Of Thementioning
confidence: 99%
“…Taken together, the techniques show the presence of flexibility of SLIV both in and out of complex. Both Hepatitis B (HBV) and HCV have also been investigated using SAXS [59,60]. SAXS data helped to support an NMR structural determination of the 6nt HBV priming loop, in which the partially stacked G16 and U17 were identified as potential residues responsible for initiating DNA synthesis [59].…”
Section: Saxsmentioning
confidence: 99%
“…Both Hepatitis B (HBV) and HCV have also been investigated using SAXS [59,60]. SAXS data helped to support an NMR structural determination of the 6nt HBV priming loop, in which the partially stacked G16 and U17 were identified as potential residues responsible for initiating DNA synthesis [59]. HCV encodes a noncoding 3 domain known as 3 X which contains a 16nt palindromic genome dimerization signal that partially overlaps with a 7nt sequence that forms a long-range interaction with a complementary site within the ORF.…”
Section: Saxsmentioning
confidence: 99%